Beyond Asylum: A Quantitative Model of Social Integration and Well-being among Refugees in Greek Local Societies - Vasileios, Eleftheriou; Charalampos, Kyriakidis; Potsiou, Chryssy (European Journal of Social Science Education and Research, 2025)
This study moves beyond theoretical frameworks to empirically test a model of social integration among refugees in Greece. While factors affecting integration are well-documented, their relative importance in this critical context remains under-quantified. This research examines the predictive power of structural factors (housing, employment) and social factors (language proficiency, host community contact) on two key outcomes: social integration and psychological well-being. Using a cross-sectional survey of 435 recognized refugees and asylum-seekers in Athens and Thessaloniki, we employed hierarchical multiple regression analyses. The findings reveal that social factors are stronger predictors of integration than structural factors. Host community contact (β = .31) and language proficiency (β = .28) were the most powerful predictors of social integration. For psychological well-being, social integration itself emerged as the strongest predictor (β = .39), mediating the effect of other social variables. The model provides a data-driven hierarchy of needs for integration, demonstrating that while structural support is essential, it is the social factors of language and community connection that most potently drive successful integration and well-being, offering clear guidance for policy and practice.
Keywords: Social Integration, Refugees, Greece, Quantitative Model, Well-being, Housing Policy, Social Capital, Migration Studies